Malware detection technology analysis and applied research of android platform - Wei-ping WEN; Rui MEI; Ge NING; Liang-liang WANG (Tongxin xuebao)
For the Android platform security problem, a mobile client and server collaborative malware detection pro-posal was proposed, where mobile client application was mainly based on permission detection technology and imple-mented lightweight testing. The server-side detection system is mainly responsible for testing suspicious samples submit-ted by the mobile terminals, meanwhile implements the functions of software behavior analysis, signature library updates, and mobile client synchronization, etc. The server-side detection techniques include permission-based detection technol-ogy, bytecode-based static detection technology and root-based dynamic detection technology. The result of the experi-ment shows that the three detection techniques can achieve better detection results.